SMS advertising the Hallyu way: drivers, acceptance and intention to receive - Dix, Steve; Jamieson, K.; Shimul, A. (Emerald Group Publishing, 2016)
© 2016, © Emerald Group Publishing Limited. Purpose – The purpose of this paper is to examine the drivers of the acceptance of short message services (SMS) advertising and how it is still relevant and active in South Korea. Design/methodology/approach – An exploratory approach was applied with convenience sample of 206 valid responses. Existing scales were used to measure consumer’s acceptance of SMS advertising, intention to receive SMS advertising and responses to SMS advertising. Findings – The findings of this study show that the utility and context of the SMS advertising as well as consumers’ trust and attitude towards the advertising are the key drivers of consumers’ acceptance of SMS advertising in South Korea. Moreover, acceptance of SMS advertising is positively associated with intention to receive the message and further behavioural responses. Research limitations/implications – The outcomes of this study would be critical for practitioners to build strategies and conduct effective and creative SMS advertising campaigns in future. Mobile marketers should emphasize on the utility and context of the message that match with the consumers’ taste and preferences. Furthermore, consumers’ personal information needs to keep private and confidential which will create trust towards the SMS advertiser and in turn generate acceptance of SMS advertising. Originality/value – This study focuses on the consumer’s willingness to receive SMS advertising and behavioural responses to SMS advertising in South Korea which has not been explored by earlier studies.